2016
DOI: 10.1142/s0129065716500076
|View full text |Cite
|
Sign up to set email alerts
|

EEG Alpha and Gamma Modulators Mediate Motion Sickness-Related Spectral Responses

Abstract: Motion sickness (MS) is a common experience of travelers. To provide insights into brain dynamics associated with MS, this study recruited 19 subjects to participate in an electroencephalogram (EEG) experiment in a virtual-reality driving environment. When riding on consecutive winding roads, subjects experienced postural instability and sensory conflict between visual and vestibular stimuli. Meanwhile, subjects rated their level of MS on a six-point scale. Independent component analysis (ICA) was used to sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 69 publications
1
44
0
Order By: Relevance
“…Some studies reported variations in the electroencephalogram (EEG) during motion sickness (Arsalan Naqvi et al, 2015; Chelen et al, 1993; Chen et al, 2010; Chuang et al, 2016; Hu et al, 1999; Lin et al, 2007; Lutz, 1979; Park et al, 2008). A variety of changes in cognitive state are associated with alterations in the EEG, including fatigue and reduced alertness (Clayton et al, 2015; Huang et al, 2016; Wascher et al, 2014).…”
Section: Prodromal Physiological Changes: Potential Physiological mentioning
confidence: 99%
“…Some studies reported variations in the electroencephalogram (EEG) during motion sickness (Arsalan Naqvi et al, 2015; Chelen et al, 1993; Chen et al, 2010; Chuang et al, 2016; Hu et al, 1999; Lin et al, 2007; Lutz, 1979; Park et al, 2008). A variety of changes in cognitive state are associated with alterations in the EEG, including fatigue and reduced alertness (Clayton et al, 2015; Huang et al, 2016; Wascher et al, 2014).…”
Section: Prodromal Physiological Changes: Potential Physiological mentioning
confidence: 99%
“…There are some prior arts about EEG and ECG change in the conditions similar to cybersickness. Chuang et al demonstrated that a higher level of motion sickness accompanied increased activation of alpha (8-13Hz) and gamma band (>32Hz) [3]. Besides, Park et al analyzed the subjects' visual fatigue caused by 3D image through the ECG experiment.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that alpha band power could be significantly related to the VR experience. The previous VR based driving simulation experiments have mainly reported changes in alpha band (8)(9)(10)(11)(12)(13) [38,39], when participants felt tired after VR experiences. The increase in alpha band power has been shown to be negatively related to cortical activity [40][41][42].…”
Section: Discussionmentioning
confidence: 99%